PERBANDINGAN HASIL PENGUKURAN GETARAN MENGGUNAKAN ACCELEROMETER TYPE PIOZOELECTRIC CRYSTAL (PCB) DENGAN TYPE MICRO ELECTRO MECHANICAL SYSTEM (MEMS) - Bhara, Firnimus (Jurnal Teknik Sipil dan Arsitektur, 2025)
The periodic vibration parameters are deviation, velocity, and acceleration, and the measuring instruments for the three parameters are called displacement pickups, velocity pickups, and accelerometers respectively. Recently, many other materials have been discovered for measuring vibrations called MEMS (Micro Electro Mechanical System) which provide an output in the form of a voltage so that it does not require an amplifier/charge amplifier. This MEMS technology accelerometer will replace the piezoelectric crystal (PCB) technology accelerometer. This research aims to determine the comparison of vibration measurement results from the two types of accelerometers. Both types of accelerometers are placed at the end of a metal plate which is clamped at the other end. The iron plate is vibrated by providing an impact and the vibration response is recorded by Dewesoft, the vibration response is also recorded in ambient conditions. From the results of vibration measurements in ambient conditions and given impact forces, these two types of accelerometers produce the same natural frequency values, while the amplitude values ??in the form of acceleration values ??have a difference of 4.75% for impact forces and 11.35% for ambient conditions.